2010
DOI: 10.1111/j.1755-3768.2009.01566.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of major eye diseases and causes of visual impairment in the adult Finnish population: a nationwide population‐based survey

Abstract: ABSTRACT.Purpose: To estimate the prevalence of cataract, glaucoma, age-related maculopathy (ARM) and diabetic retinopathy (DR) in the adult Finnish population. Methods: A representative cross-sectional sample of the Finnish population aged 30 years and older. Of the 7979 eligible people, 7413 (93%) were interviewed and ⁄ or examined. The interview included self-reported doctor-made diagnoses of cataract, glaucoma, degenerative fundus changes (mainly ARM) or DR. Information on self-reported eye diseases was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
5
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 59 publications
(133 reference statements)
6
54
5
7
Order By: Relevance
“…Moreover, many of our other findings are also in agreement with previous studies, e.g. our overall cataract prevalence is comparable to a recent population-based study in Finland [17], and the risk of sympathomimetic drugs or inhaled glucocorticoids for cataractogenesis is well known (for a recent review see [18]). The preferred sequence of cataract formation followed by AMD is also in line with previous observations of an association of cataract surgery with late AMD [19].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, many of our other findings are also in agreement with previous studies, e.g. our overall cataract prevalence is comparable to a recent population-based study in Finland [17], and the risk of sympathomimetic drugs or inhaled glucocorticoids for cataractogenesis is well known (for a recent review see [18]). The preferred sequence of cataract formation followed by AMD is also in line with previous observations of an association of cataract surgery with late AMD [19].…”
Section: Discussionsupporting
confidence: 93%
“…These observations have been supported by several other studies that have linked lutein and zeaxanthin concentrations to the reduction of cataracts in North Indian population [82], in older American women [83] and in Australian population [84]. Recent studies also reported the prevalence of major eye diseases and showed that high plasma concentrations of lutein and zeaxanthin reduced the risk of age-related cataract in the elderly Finnish population by about 41% [85,86]. Studies involving older Europeans from Norway, Estonia, United Kingdom, France, Italy, Greece and Spain have reported high AMD prevalence (4% to 12%) depending on age [87].…”
Section: Lutein and Zeaxanthin Carotenoidssupporting
confidence: 63%
“…The prevalence is reported to be 3.5–40 % depending on age for AMD, 3.3–14 % for glaucoma, and 4.4–20.9 % for diabetic retinopathy [221]. The prevalence for cataract increases with age and is over 40 % in subjects older than 75 years [222224]. …”
Section: Judgement Of the Evidence Regarding Individual Diseasesmentioning
confidence: 99%